Heparin Resistance in SARS-CoV-2 Infected Patients with Venous Thromboembolism. (December 2022) - Chau, Terence; Joseph, Merlyn; Solomon, Diana M.; Lee, Bryan; Igneri, Lauren A.
Introduction: Heparin resistance has been reported in coronavirus disease 2019 (COVID-19) patients receiving intravenous unfractionated heparin (IV UFH). Anti-Xa monitoring of IV UFH has been suggested over activated partial thromboplastin times due to laboratory interference from elevated factor VIII and fibrinogen levels in COVID-19 patients. Information on heparin resistance with anti-Xa monitoring in COVID-19 patients with confirmed venous thromboembolism (VTE) is lacking.Methods: In this retrospective cohort study of patients with radiographically confirmed VTE, IV UFH dosage requirements in COVID-19 positive patients were compared with COVID-19 negative patients. The primary endpoint was the IV UFH dose needed to achieve a therapeutic anti-Xa level. Secondary endpoints included time to therapeutic anti-Xa, number of dose adjustments to achieve therapeutic anti-Xa, and bleeding.Results: Sixty-four patients with confirmed VTE were included (20 patients COVID-19 positive, 44 patients COVID-19 negative). Eighty-five percent (17 of 20) of COVID-19 positive patients achieved anti-Xa ≥ 0.3 units/mL with the first anti-Xa level drawn post-IV UFH infusion initiation. The median UFH dose needed to achieve first therapeutic anti-Xa was similar between COVID-19 positive and COVID-19 negative patients (median [IQR]: 18 units/kg/hour [18-18] vs 18 units/kg/hour [18-18], P  = .423). The median number of dose adjustments and time to achieve therapeutic anti-Xa were also similar between the 2 groups. The frequency of patients receiving IV UFH of more 35 000 units/day did not differ between the 2 groups. Two cases of clinically significant heparin resistance in the COVID-19 positive group were identified.Conclusions: During the first wave of COVID-19, heparin dose and time to therapeutic anticoagulation appeared to be similar between COVID-19 positive and COVID-19 negative patients monitored by anti-Xa at our institution. More studies are required to evaluate clinically significant heparin resistance in the context of the wide range of viral variants which developed, and beyond the population observed in this single center retrospective study.